Hyundai Investment on Electric Vehicles in Indonesia: a Push-Pull Factor Analysis - Achmad Ismail; Darynaufal Mulyaman (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2021)
The electric vehicle trend globally made mobile automakers preparing another strategy. Nonetheless for Hyundai as South Korean biggest automaker with their success in the domestic market attracting Hyundai to expand their business. On the other side, Indonesia as the biggest economy in ASEAN demands continuous growth of its economy and expecting economy drive from foreign direct investment (FDI) and seeing the global trend despite lack of electric vehicle facilities and technology. This article analyzes why Hyundai decided to make a direct investment in Indonesia regarding the electric vehicle. This article tried to break down the premises through the push-pull factor in order to give an argument about Hyundai reasons in Indonesia.